Mitigating the open vessel artefact in centrifuge-based measurement of embolism resistance. (1st August 2018) - López, Rosana; Nolf, Markus; Duursma, Remko A; Badel, Eric; Flavel, Richard J; Cochard, Hervé; Choat, Brendan
Abstract: Centrifuge-based techniques to assess xylem vulnerability to embolism are increasingly being used, although we are yet to reach a consensus on the nature and extent of artefactual embolism observed in some angiosperm species. In particular, there is disagreement over whether these artefacts influence both the spin (Cavitron) and static versions of the centrifuge technique equally. We tested two methods for inducing embolism: bench dehydration and centrifugation. We used three methods to measure the resulting loss of conductivity: gravimetric flow measured in bench-dehydrated and centrifuged samples (static centrifuge), in situ flow measured under tension during spinning in the centrifuge (Cavitron) and direct imaging using X-ray computed microtomography (microCT) observations in stems of two species of Hakea that differ in vessel length. Both centrifuge techniques were prone to artefactual embolism in samples with maximum vessel length longer than, or similar to, the centrifuge rotor diameter. Observations with microCT indicated that this artefactual embolism occurred in the outermost portions of samples. The artefact was largely eliminated if flow was measured in an excised central part of the segment in the static centrifuge or starting measurements with the Cavitron at pressures lower than the threshold of embolism formation in open vessels. The simulations of loss of conductivity in centrifuged samples with a new model, CAVITOPEN, confirmed that the impact of open vessels on the vulnerability to embolism curve was higher when vessels were long, samples short and when embolism is formed in open vessels at less negative pressures. This model also offers a robust and quantitative tool to test and correct for artefactual embolism at low xylem tensions.